Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2025)
Table of Content: 1. The role of institutional change in improving the quality of health services: An applied study At the Civil Hospital in Khamis Mushait Mr. Ayidh Hamoud Alshahrani, Mr. Abdullah Mohammed Alshehri, Mr. Saad Awad Alqahtani 2. Strategies for solving administrative problems using machine learning technology on Amazon Ms. Rana Mohammed Alsuhaimi, Ms. Shomoukh Abdullah Aldhafeeri, Ms. Maha Mohammed Alotaibi, Dr. Futoon Ahmed Othman 3. Accounting Environment Readiness for The Application of International Financial Reporting Standards (IFRS) in KSA: An analysis Study (2016 - 2017) Asst-Prof. Shihabeldeen Mohamed Ahmed ,Asst-Prof. Abu Baker Ahmed Yousif 4. The Role of the Knowledge Economy in Developing the Export Sector in the Kingdom of Saudi Arabia During Period (2000-2021) Co-Prof. Sahar Hassan Khayat ,Ms. Ghadah Muhammed AlAmri 5. International legal mechanisms to protect the environment from climate change Mr. Abdulmajeed Motib Alotaebi 6. The crime of human trafficking (A comparative legal study between Egypt and Saudi Arabia) Dr. Reem Gomaa Zekry 7. Legal regulations to ensure the satisfaction of living organ donors Mr. "Mohammad Ali" Jehad Sarah 8. The relationship between accreditation standards and organizational excellence and their role in the excellence of administrative leadership Dr. Norah Abdulaziz Ibrahim Alsaleem